Innovation policy instruments in Rhône-Alpes - key challenges and future orientations - Czyżewska, Dorota (Economics and Business Review, 2013)
The paper is an attempt to show to what extent selected innovation policy instruments in the French Rhône-Alpes region are drivers of regional competitiveness. The aim of the paper is threefold. Firstly, an overview of recent regional economic performance, as well as key socio-economic conditions are presented using available regional statistical data. Secondly, regional innovation policy governance is presented as a foundation of regional innovation policy and selected innovation policy measures: competitiveness clusters, research clusters, regional clusters and the ARDI are described as instruments of regional innovation policy to foster regional competitiveness. Thirdly, some crucial challenges and recommendations are proposed in order to increase the effectiveness of regional innovation policy. (original abstract)